The experience of virtualization and university culture: A qualitative study of Tehran universities - F. Lolaee; S. Bastani; M. Farasatkhah (Taḥqīqāt-i Farhangī-i Īrān)
The dramatic changes that have taken place in the field of information and communication in the present age have led to fundamental changes in various parts of human life. The important point is that the emergence of virtual technologies is not just a conventional technical development but contains a cultural nature. The university is also one of the institutions that has been particularly affected by these developments. Such conditions have changed the relationship between students and professors, their way of accessing information and resources, creating and sharing educational content, and so on. The purpose of this article is to study the experience of virtualization and academic culture. This is a qualitative research that has applied a phenomenological method with semi-structured interviews. Participants were purposefully selected from among students, graduates, faculty members, and university administrators. Data were analyzed using the thematic analysis technique which resulted in 10 semantic clusters. The results of the interviews show a duality in responses, with some interviewees emphasizing the functions of virtualization in university culture in terms of communication, education and lifestyle. They believe that virtualization has opened doors to universities. The other category, however, explains the negative consequences of virtualization in academic culture and its various dimensions. The results indicate that with virtualization, important changes have occurred in various dimensions of the university culture that should be considered at micro and macro levels.